Applying Auditory Intellectually Repetition (Air) Model in Cell Material for Student Result - Sutiyani, Iis; Sukaesih, Sri; Mustikaningtyas, Dewi (Journal of Biology Education, 2017)
The purpose of this study to describe of applying Auditory Intellectually Repetition (AIR) model in cellmaterial for students result. This study used Quasy Experimental research by Non-Equivalent ControlGroup design. Sample is determined by convinience sampling, that is class XI MIA 3(control class) and XIMIA 4 (experimental class). The result of this research show that learning using AIR in experimental class ishigher than with control class. Analysis of pretest and posttest examine t of tcount 7,426>ttable 1,988 withsignificant level 0,05, so it can difference of increase study result in both class. Examine N-Gainexperimental class 84% in high category, and control class 41% in middle category. Examine t average NGaintcount 4,80>ttable 1,988. Analysis student activities in experimental class is higher than control classwhich has percentage of very active and active criterias for experimental class 93.18% and 78.57% for controlclass. Analysis of psychomotoric study result in experimental class is 14% in excellent category, 84% in goodcategory, whereas control class gets persentage 5% in excellent category and 71% in good category. Very goodlevel of implementation AIR model with in average 86%. Teachers and students also respond very well toAIR. The conclusion of this study results was apply AIR model in cell material positive effect for studentresult.